Stockholm Syndrome Dan Pemaafan (Forgiveness) Pada Remaja Perempuan Yang Mengalami Kekerasan Dalam Pacaran (Intimate Patner Violence) - Ayuning Atmasari; Dara Dwi April Liandani (JURNAL PSIMAWA, 2023)
Stockholm Syndromeis a paradox conditions (predictable) with psychological, where it will arisea strong bond between the victims of the perpetrators violence, this bond includes the victim's senseagainst the perpetrators, protecting the hassles dating persecuting it, blame yourself ascauses of violence, and deny orminimizing the violence that occur (Agarwalk, 2017). This researchaim to know the picture Stockholm Syndrome and forgiveness of women teenagers who have violent in dating.The type of research conducted is descriptive qualitative research, with subjects of two people The person who has violent in the dating turns out to be very bad impact on the victim of the physical and psychological terms, in terms of physical victims will suffer the bound and blessing in the body of the victim's body, then from the psychological condition will make the victim feel anxious, unstable emotions such as crying suddenly, and not focused. However, even though the second demonk of the subject still retains its relationship with the reason it feels comfortable and very love to his partner so that it is what makes. The two subjects are able to survive and forgive all the acts of violence by his partner. Keywords: teenagers who have violent in dating,Stocholm Syndrome, forgiveness